THE ASTOUNDING CONSISTENCY OF THE CALCULATION METHOD FOR THE CIRCUMFERENCE BETWEEN ANCIENT EGYPT AND ANCIENT CHINA - Tian Bin; Wang Fang (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The value of ? was 3, which had been well documented in ancient classics and archaeological discoveries, including the Old Testament, ancient Egypt archaeology and ancient Chinese mathematical literature. The majority argues that this can be attributed to undeveloped, imprecise ancient mathematics, while the impeccable pyramids, withstanding 4 millennia, and the Dujiangyan, the large-scale project for irrigation and flood control, constructed around 256BC, still in use today, indicate that ancient mathematics thousands of years ago, was able to achieve accurate calculation. Nevertheless, this raises several questions, how to achieve accurate calculation when the value of ? is 3? Is it possible that there is a huge difference between the ancient method of calculation and the method used in contemporary times? Based on extensive exploration of the Chinese mathematical classic Zhoubi Suanjing, multiplication table, and ancient Egyptian multiplication discovered in ancient Egypt archaeology, researchers have found the precise calculation method for computing the circumference of circles as ? equals 3. Firstly, calculating the main value of the circumference when ? was 3, then computing the difference value of the circumference by the multiples "7, 8 and 9" and the accurate value of circumference of circles obtained with the combinations of the main value and the D value, which exhibits a high degree of precision that is no less than that of our current mathematical methodologies. This discovery, promoting more a profound understanding level of human civilization, not only fundamentally, originally facilitates the studies of ancient and modern mathematics but also serves as mathematical grounds for multiple fields research, including archaeology, history and theology.